ALAT POLINASI DAN AKTIVITAS TERHADAP PRODUKSI BENIH BAWANG DAUN (Alium fistolosum) - Uun SUMPENA (Universitas Wahid Hasyim, 2014)
Experiment was conducted to find out number of pollination activities and material of artificial pollination on Spring onion seed production. A Factorial Design Randomized Block with 5 replication was set up. The treatments consisted of two levels of number of pollination activities (two and three time per weeks) and two levels of pollination artificial material (soft brush and gun sprayer) and control. Five treatments including control were studied. Research results showed that 3 time per week number of pollination activities with gun sprayer material of artificial pollination significantly increased total yield of Spring onion seed to rainy season in highland. Keywords: Number of pollination activities, pollination artificial, spring onion.